Smart grids : security and privacy issues - Boroojeni, Kianoosh G., 1989-; Amini, M. Hadi; Iyengar, S. S. (Springer, 2016)
This book provides a thorough treatment of privacy and security issues for researchers in the fields of smart grids, engineering, and computer science. It presents comprehensive insight to understanding the big picture of privacy and security challenges in both physical and information aspects of smart grids. The authors utilize an advanced interdisciplinary approach to address the existing security and privacy issues and propose legitimate countermeasures for each of them in the standpoint of both computing and electrical engineering. The proposed methods are theoretically proofed by mathematical tools and illustrated by real-world examples. Provides the theoretical means for maintaining the privacy and security of smart grids Provides comprehensive location privacy preserving mechanisms for end-users and mobile users in the context of smart grids Evaluates the privacy and security concerns of both physical and information layers Presents the state-of-the-art method for economic dispatch in the future power systems using oblivious routing network design.
Keywords: Smart power grids -- Security measures.; Public utilities -- Security measures.; Privacy, Right of.; Records -- Access control.; elektronické knihy; electronic books